PENGARUH TUNJANGAN KESEJAHTERAAN, DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Andriani, Irma; Prima Putri, Nelly (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to determine the effect of Welfare Benefits and Work Life Balance on Employee Performance through Organizational Citizenship Behavior as an Intervening Variable. The data collection method is through saturated sampling, with a sample of 66 employees. The method used is Structure Equation Modeling (SEM) with Partial Least Square (PLS) 4.0. The test results show that: Welfare benefits and work life balance influence organizational citizenship behavior and employee performance. Organizational citizenship behavior influences employee performance. Welfare benefits and work life balance influence employee performance mediated by organizational citizenship behavior. The author suggests that companies pay attention to employee work safety so that employee performance increases.Keywords: Welfare Benefits, Work Life Balance, Employee Performance